(3HZjI GdYdeGA hGdQhGg aj GdPjd Ydi cJGH TjNi aj GdbVGgs - (3TeS GdOjf CHi GdNjQ eMeO Hf eMeO Hf YHO GdQMef Hf eMeO GdSNGhis; (3TgGH GdOjf CHh GdaVd CMeO Hf Ydj Hf MLQ GdYSbdGfi,J (B852 (3g` s
(3ChdgG (B:s
(3bGd SjOfG hTjNfG GdMGaX GdSNGhi GdMeO ddg GdMce GdYOd hHYO agPG LRA GaQOJ ajg eG dPcQ ef JCNQ s
(3BNQgG (B:s
(3Ke Oaf HJQHJg hde jdHK Cf GSJbQ hdOg GdHOQi ai hXjaJg hhGab GdaQGZ ef cJGHJg s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B32 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B46 s
Keywords: (3GdJGQjNs